Sistem Informasi Transaksi dalam P2P di Pasar Cryptocurrency Binance - Mintauli Debataraja; Elian Juan Gonzales; Amanda Septia Kosaanah (UNIVERSITAS RAHARJA, 2022)
With this research to determine the effect of public literacy in investing, the most common are currency, paper money and coins. Now the blockchain technology that we hear more often, namely with cryptocurrencies, has made many meanings of the benefits of profit because it is without the costs of administrative services, without intermediaries, and delays. In this case, one of them is the Binance Platform, the Fintech P2P lending Ecosystem and digital transaction system are growing very quickly and become one of the cashless payment options, an alternative choice for new tariff categories because of the multiple advantages of fast and technology-based processes which are the supporting culture of the MSME generation. Cryptocurrency despite very significant progress but not many countries have legalized it as a legal medium of exchange. With the influence of information systems science, namely by knowing more about the extent of acceptance of cryptocurrencies in society in terms of social finance